(3GdcGaj aj TQM GdgGOi aj GdfMhs - (3YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH GdNRQLj GdRfLGfj,J (B655 (3g` s ((3TjQGR s)
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdCcQe GdPi Yde HGdbde Yde GdEfSGf eGde jYde CeG de jYde CeG HYO aEf CMb eG UQaJ Edjg Gdgee gh Yde GdfMh s
(3BNQgG (B:s
(3ef GQGO GSJbUGA aYdjg HcJHfG GdeUfaI ai gPG Gdaf hGddg CYde HGdMbGFb hGdMeO ddg GdPi CfRd Ydi YHOg GdcJGH Ydi JhajbfG dEJeGe gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3HChdgG agQSs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B216s
Keywords: (3GdfMhs